Alone in paradise: a new genus and species of Hirmoneurini tangle-veined flies (Diptera, Nemestrinidae) in South America - Pujol-Luz, José Roberto; Lamas, Carlos José Einicker (Zootaxa, 2023)
A new genus and new species of tangle-veined flies of the tribe Hirmoneurini (Nemestrinidae), Bernardia xenomorpha gen. et sp. nov., is described from the highland savannas of Brazil. This represents the first record of this tribe from the Southern Hemisphere. The new taxon is compared with the related genera and species of Hirmoneurinae. Bernardia xenomorpha gen. et sp. nov. fits perfectly in the diagnosis of the subfamily, especially by the reduction of the hypandrium and by having the proboscis reduced and, in the tribe Hirmoneurini, by having the frons projected forward and covered by dense pilosity. Bernardia xenomorpha gen. et sp. nov. is distinguished from the other species of Hirmoneurinae, mainly by the length of the proboscis, which reaches the first pair of coxae, while in the other species the proboscis does not exceed the length of the head and, by the U-shaped genital fork, with simple (not bifurcate) arms. An identification key for the American subfamilies, tribes, and genera of Nemestrinidae is also included.